Fine structures in the intensity dependence of excitation and ionization probabilities of hydrogen atoms in intense 800-nm laser pulses - Li, Qianguang; Tong, Xiao-Min; Morishita, Toru; Wei, Hui; Lin, Chii Dong (My University, 2014)
We studied the elementary processes of excitation and ionization of atomic hydrogen in an intense 800-nm pulse with intensity in the 1.0 to 2.5×10[superscript 14] W/cm² range. By analyzing excitation as a continuation of above-threshold ionization (ATI) into the below-threshold negative energy region, we show that modulation of excitation probability and the well-known shift of low-energy ATI peaks vs laser intensity share the same origin. Modulation of excitation probability is a general strong field phenomenon and is shown to be a consequence of channel closing in multiphoton ionization processes. Furthermore, the excited states populated in general have large orbital angular momentum and they are stable against ionization by the intense 800-nm laser—they are the underlying reason for population trapping of atoms and molecules in intense laser fields.
Keywords: Excitation; Ionization; Hydrogen; Above-threshold ionization; 800-nm laser pulses